Constituents of the Essential Oil and Fatty Acid from Rare and Endangered Plant Magnolia kwangsiensis Figlar & Noot. Issue 1 (2nd January 2019) - Zheng, Yan-Fei; Liu, Xiong-Min; Zhang, Qiang; Lai, Fang; Ma, Li
Abstract: Magnolia kwangsiensis Figlar & Noot., is a rare and endangered plant. The essential oils were obtained using hydrodistillation from peel and aril, and fatty acids were extracted by ultrasound-assisted extraction. Essential oils and fatty acids were analyzed by GC/MS. Results showed that the yield of essential oil was 0.10%, and twenty- two compounds was identified., main constituents included cis -β-ocimene (30.80%), p-menth-1-ene (17.76%), α-terpinene (10.15%), β-myrcene (7.03%), and α-terpineol (5.18%) and so on in the peel. Yield of essential oil was 4.91%, and the major constituents included cis -β-ocimene (56.03%), β-phellandrene (10.96%), α-terpinene(6.37%), α-phellandrene(6.16%), and β-myrcene (6.04%) in the aril. Cis -β-ocimene was the highest concentration both in the peel oil and aril oil. The yield of lipid was 33.00% from aril obtained, and 11 fatty acids were identified, main fatty acids were 9, 12-octadecadienoic acid 49.52%, hexadecanoic acid 32.27%, octadecenoic acid 10.24% and octadecanoic acid 4.49%. Yield of lipid was 33.00% from kernel obtained, main fatty acids were 9, 12-octadecadienoic acid 56.91%, hexadecanoic acid 25.27%, octadecenoic acid 12.09% and octadecanoic acid 5.63%. The content of unsaturated fatty acids was 62.22% in aril lipid and 69.03% in kernel lipid.